EVIDENCE OF CUSTOMERS’ PERCEPTIONS TOWARD THE USAGE OF SOCIAL NETWORKING SITES AS E-BUSINESS MECHANISM IN UAE - Beenu Mago; Pooja Trivedi (European Scientific Journal, ESJ, 2014)
This Quantitative research paper studies the determinants like trust and loyalty, Information Quality, Consistency of information; feedback mechanism and relationship management which if instigated through social networking sites can significantly bind the customers with the organizations and finally help the organizations to retain their customers. Organizations in UAE have started investing sizable amounts of financial and human capital towards the development and implementation of innovative technological solutions for communication with the customers. However, most of these businesses use social media as a promotional tool rather than using it as e-business tool to create social CRM. The pressure on companies to embrace social media is fierce.